Recognizing the distinct cytomorphologic features of solid pseudopapillary neoplasm of the pancreas - Haque, Saadiya; Dietz, Robin; Perez, Mia C. N. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare low-grade malignant tumor with an indolent clinical course and a favorable prognosis that is most commonly seen in young women of reproductive age. We present a case of SPN in a middle-aged man, diagnosed on a limited cytology specimen. Interestingly, this tumor has unique cytomorphologic findings in fine needle aspiration cytology smears, which help distinguish it from other pancreatic lesions. The presence of fibrovascular cores lined by loosely cohesive monomorphic neoplastic cells is a reliable cytomorphologic feature on aspiration cytology. Recognition of this characteristic finding is crucial for the diagnosis of this entity, especially when it presents in unexpected patient populations or when faced with scant cytology specimens. This report focuses on the distinguishing characteristics of SPN and how they compare and contrast with other pancreatic lesions that are in the differential diagnosis of SPN.